Theory-Based Education and Postural Ergonomic Behaviours of Computer Operators: A Randomized Controlled Trial From Iran. - TavafİAn, Sedigheh; ZeİDİ, Isa 1-Mohammadi; HeİDarnİA, Ali Reza (Turkish Journal of Physical Medicine & Rehabilitation / Turkiye Fiziksel Tip ve Rehabilitasyon Dergisi, 2012)
Objective: This study evaluated the effects of a designed stage-matched educational program based on stage of change model on knowledge, attitude, intention and behaviours of Iranian computer users. Materials and Methods: Of four computer stations affiliated to Qazvin University of Medical Sciences, two sites were randomly selected as intervention and control ones, each 75 eligible computer users were randomly selected and if satisfied, they were entered into the study. The participants working in intervention site received the stage-matched intervention. Questionnaires of stages of change, ergo-knowledge/attitude, intent towards ergonomic and postural behaviour, Rapid Upper Limp Assessment (RULA), Visual Analogue Scale (VAS), and the Nordic questionnaire were completed at baseline and 3-month follow up. Data were entered to SPSS and analyzed through descriptive and analytical statistics. Results: A total of 150 participants with a mean age of 31.6 years (SD=7.0) took part in the study of which 67% (n=101) were female. The intervention group, compared to control group, showed significant improvements in stages of change (p<0.001), ergo-knowledge (p<0.001), attitude (p< 0.05), intent (p<0.001), and perceived behaviours control (p<0.001). Conclusion: This study revealed beneficial impact of the educational program in occupational setting. This designed stage-matched educational program could be practiced by computer workstations.